2018
DOI: 10.1016/j.acmx.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Análisis demográfico de una clínica de cardiopatías congénitas del Instituto Mexicano del Seguro Social, con interés en el adulto

Abstract: CHD is a late diagnosis; it is necessary to create a national register to promote new health policies and a rational distribution of resources for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…VSD is the third most common isolated defect, after patent ductus arteriosus (PDA) and inter-atrial communication (IAC) [ 17 ]. Some studies have reported a prevalence of children under 6 years of age with VSD of between 9.3 and 10.29% in Mexico [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…VSD is the third most common isolated defect, after patent ductus arteriosus (PDA) and inter-atrial communication (IAC) [ 17 ]. Some studies have reported a prevalence of children under 6 years of age with VSD of between 9.3 and 10.29% in Mexico [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported an increasing prevalence of congenital heart diseases in Mexico, with variations in the prevalence rates depending on the specific type of heart disease and the region of the country [14]. Genetic factors, such as consanguinity and a high prevalence of certain gene mutations, may contribute to the increased prevalence of congenital heart diseases in the Mexican population [15]. Environmental factors, including maternal use of medications during pregnancy, exposure to infections, and poor prenatal care, may also play a role [16].…”
Section: Discussionmentioning
confidence: 99%
“…nacimientos al año, estimamos alrededor de 20,000 niños con enfermedad cardiaca congénita, lo que hace a estas patologías un problema de salud importante. 2 La presentación de cardiopatías congénitas en gemelos al parecer no es tan común y el abordaje de la lesión y el pronóstico tienen relación con la edad gestacional y el peso al nacer. 3 www.medigraphic.com/actamedica www.medigraphic.org.mx…”
Section: Introductionunclassified